Modernity of Malaysian Sarawak literature in Chinese from the post-colonial perspective - Tiong, Nga Houng (2014)
Academic studies of Malaysian Sarawak literature in Chinese (Sarawak literature in Chinese) are still limited. In Malaysia, Singapore and Taiwan, perceptions of scholars regarding Sarawak literature in Chinese are mostly focused on the diasporic modernism aesthetics as expressed in the works of Zhang Guixing and Li Yongping. As for academicians in China, their discourses on local Sarawakian poets and writers such as Wu An and Liang Fang are more inclined towards the perspective of traditional realism. As such, literary scholars have often paid little attention to the role of Sarawak literature in Chinese in the development process of colonialism. From the internal perspective, due to the inadequate system of literary criticism, our understanding of Sarawak literature in Chinese is limited to the scanty information available through the anti-colonialism – realism discourses of Tian Nong and Huang Fei. From the external viewpoint, the understanding tends to resemble the Orientalist perceptions of the Western academicians in the fields of historical and anthropological studies, and in more specific terms, such an understanding is but the curiosity of exploring the novelty world of Borneo (referring generally to East Malaysia). As a literary stream of a former colony, Sarawak literature in Chinese undoubtedly has the beginning of its modernity brought about by the historical circumstances of colonialism, and subsequently its modernistic logic was consolidated in the megatrend of anti-colonialism. Therefore, this thesis aims at exploring whether Sarawak literature in Chinese had undergone a period of modernity during the colonial rule that lasted for 122 years. It also seeks to discuss the influence of colonialism on Sarawak literature in Chinese in terms of the formation of its modernistic contents, and thereafter to further interpret Sarawak literature in Chinese from two dimensions: the intrinsic contents of thoughts and the aesthetic aspects. Furthermore, by adopting the post-colonial perspective, the thesis also attempts to explore the specific connotations of modernity in Sarawak literature in Chinese and its conditions in the post-colonial period. This thesis adopts text analysis as the main method to study works of fiction and poetry in Sarawak literature in Chinese by local writers including Liang Fang, Wu An, Rong Rong, Hei Yan, Ju Yaoru, Zhang Yiping, Li Sheng, Zhang Guixing, Li Yongping, Huang Zerong and Ye Shui. It is an attempt to explore the connotations of modernity in Sarawak literature in Chinese. Results of the study show that in terms of the intrinsic contents of thoughts, works of realism in Sarawak literature in Chinese can be summarized into six modernistic attributes: critique of colonial culture and coloniality; revelation of contradictions between old and new thoughts; critique of individualism; progress and critique of modernisation; praises for the spirit of humanitarianism; and the spirits of optimism, proactive progress as well as radicalism.For works of modernism, the modernistic thoughts as reflected can be examined from two aspects: firstly the introspection of capitalism and bourgeoisie class during the colonial rule period, and secondly the exploration into the „modernistic‟ consciousness of the modern people under the impact of modernisation. From the aesthetic dimension, works of both realism and modernism do show creativity and a certain extent of reflection in terms of form, technique and language; however, works of modernism / postmodernism have demonstrated more diverse techniques and have even ventured into new themes of creative works including cross-ethnic writing, modernistic writing of „sex‟ and concern for environmental problems. The issues of modernity, coloniality and post-colonial phenomena as discussed in this thesis are concerned with thoughts as well as aesthetics.